Social And Cultural Life in Kungrad District in The Years of Independence - Kayupova Malika (Zien Journals, 2021)
This article is about Kungrad, an industrial town that made a significant contribution to the development of the Republic of Karakalpakstan during the years of independence. In this article, we have made a comparative analysis of the development of the city of Kungrad in the pre-independence and postindependence periods and drawn our own conclusions.
Keywords: Kungrad; monuments; socio-economical potencial; region; intependence